2008
DOI: 10.1210/en.2008-0315
|View full text |Cite
|
Sign up to set email alerts
|

Graded Hedgehog and Fibroblast Growth Factor Signaling Independently Regulate Pituitary Cell Fates and Help Establish the Pars Distalis and Pars Intermedia of the Zebrafish Adenohypophysis

Abstract: The vertebrate adenohypophysis forms as a placode at the anterior margin of the neural plate, requiring both hedgehog (Hh) and fibroblast growth factor (Fgf) mediated cell-cell signaling for induction and survival of endocrine cell types. Using small molecule inhibitors to modulate signaling levels during zebrafish development we show that graded Hh and Fgf signaling independently help establish the two subdomains of the adenohypophysis, the anteriorly located pars distalis (PD) and the posterior pars intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Pax7 is another member of the Pax family and expressed in developing muscle and brain, and Pax7 expression is maintained after birth in both tissues 5154. Here, we show that Pax7 is expressed in adult mouse pituitary gland, consistent with a previous report that Pax7 is expressed in the precursors of the pituitary gland of the zebrafish embryo 55. Taken together with our detection of Pax7 in the macaque pituitary, Pax7 expression in the pituitary gland appears to be well conserved in the macaque and human pituitary as a precursor to a corticotroph/melanotroph population in the intermediate lobe (Suppl.…”
Section: Discussionsupporting
confidence: 92%
“…Pax7 is another member of the Pax family and expressed in developing muscle and brain, and Pax7 expression is maintained after birth in both tissues 5154. Here, we show that Pax7 is expressed in adult mouse pituitary gland, consistent with a previous report that Pax7 is expressed in the precursors of the pituitary gland of the zebrafish embryo 55. Taken together with our detection of Pax7 in the macaque pituitary, Pax7 expression in the pituitary gland appears to be well conserved in the macaque and human pituitary as a precursor to a corticotroph/melanotroph population in the intermediate lobe (Suppl.…”
Section: Discussionsupporting
confidence: 92%
“…S2A,B, in the supplementary material; data not shown). Our previous work showed that Hh dosage regulates endocrine cell differentiation, with Prolactin-(Prl), Adrenocorticotropic hormone-(Acth; Pomca -Zebrafish Information Network) and Growth hormone-(Gh; Gh1 -Zebrafish Information Network) secreting cells being the most sensitive to reduced Hh signaling levels (Guner et al, 2008). Consistent with a mild loss of Hh signaling in uml(boc) mutants, gh-expressing cells were absent, acth-and prl-expressing cells…”
Section: Boc Function Is Necessary For Pituitary Development Early Mmentioning
confidence: 82%
“…S2 in the supplementary material) (Guner et al, 2008;Devine et al, 2009), suggest a novel role for Boc in Hh-mediated pituitary patterning. Low-level boc expression was detected in the placode region prior to 24 hpf, however boc expression was not seen in the placode by 36 hpf.…”
Section: Boc and Pituitary Developmentmentioning
confidence: 99%
“…2B). nxk2.2a expression is induced by Hh signaling and pax3a expression is repressed by Hh (Guner et al, 2008; Liem et al, 1995). The polarity of the vertebrate neural tube is established by a gradient of Shh (Briscoe and Ericson, 1999), and we wondered if Rest knockdown enhanced expression of other Hh target genes within the developing neural tube.…”
Section: Resultsmentioning
confidence: 99%